The impact of innate accruals quality on the future market value moderated by dividend policy - Muljanto Siladjaja; Yuli Anwar (Asian Journal of Accounting Research, 2020)
The purpose of this study is to test and prove how the quality of innate accruals can make a significant contribution to the prospect of future market value for manufacturing industries.This research used multiple regression method by gathering all observation data on a go public company in the industrial manufacturing sector.The results of this test can show that the dividend policy helps reduce the use of accruals to increase investor perceptions about the prospects of the company's future period, especially the value of earnings informativeness, including valid information about the actual fundamental conditions. These results reflect high innate accruals quality, so the use of low accruals, especially in reporting earnings.This test uses a measurement of a constant growth rate with the calculation of the indicator g in the next five-year period, and the proof has secondary data abnormalities reflecting a very high level of variation in the use of accruals. As an implication of the data that is not normal, it causes a large amount of data pruning through outlier tests. Samples that qualify for processing are 180 from 384 data.By calculating the value of the dividend payout with the growth rate, the estimated future market price can be done with reasonable accuracy.